A PROPORTIONAL ALLOCATION OF FORMATIVE AND SUMMATIVE ASSESSMENT: A Quest of Shaping an Effective Assessment Policy - Sabilil Muttaqin (Hikmah: Journal of Islamic Studies, 2020)
Abstract This paper outlines and discusses most of the literatures on formative and summative assessment. It considers some of the key features of both formative and summative assessment as a means of evaluating teaching and learning processes. This study suggests that both types of assessment should be proportionally designed and aligned with learning goals. More importantly, this study proposes three key aspects of assessment that should be considered in designing effective assessment policy: (a) assessment forms an integral part of planning, assessing, and reporting, (b) the use of assessment as a means to monitor the progress of student learning and achievement, (c) assessment as a tool to determine the effectiveness of teaching. The three aspects of assessment policy can help educational leaders to design a proportional formative and summative assessment for an effective assessment policy. Abstrak Artikel ini memaparkan dan mendiskusikan literatur-literatur tentang penilaian formatif dan sumatif. Artikel ini juga menyuguhkan gambaran penting penilaian formatif dan sumatif sebagai alat evaluasi pengajaran dan proses pembelajaran. Kajian ini menemukan bahwa kedua jenis penilaian tersebut harus didesain secara proporsional dan harus sejalan dengan tujuan pembelajaran. Lebih penting lagi, kajian ini menawarkan tiga aspek penting yang harus dipertimbangkan dalam merancang kebijakan penilaian yang efektif.: (a) penilaian harus membentuk sebuah bagian integral dari perencanaan, penilaian dan pelaporan, (b) penggunaan penilaian sebagai alat untuk memonitor progress pembelajaran siswa dan pecapaiannya, (c) penilaian sebagai alat untuk menentukan efektivitas mengajar. Tiga aspek kebijakan penilaian tersebut dapat membantu pemimpin pendidikan untuk merancang penilaian formatif dan sumatif yang proporsional untuk sebuah kebijakan penilaian yang efektif.